1990
DOI: 10.1007/bf01840386
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fractional cascading

Abstract: The problem of searching for a key in many ordered lists arises frequently in computational geometry. Chazelle and Guibas recently introduced fractional cascading as a general technique for solving this type of problem. In this paper we show that fractional cascading also supports insertions into and deletions from the lists efficiently. More specifically, we show that a search for a key in n lists takes time O(log N+ n log log N) and an insertion or deletion takes time O(log log N). Here N is the total size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 24 publications
1
116
0
3
Order By: Relevance
“…The upper bound for this problem is slightly larger, amortised O(log n log log n) using fractional cascading [31], yet for dominance queries it is O(log n/ log log n) using [29,40], matching our lower bound.…”
Section: Applicationssupporting
confidence: 68%
“…The upper bound for this problem is slightly larger, amortised O(log n log log n) using fractional cascading [31], yet for dominance queries it is O(log n/ log log n) using [29,40], matching our lower bound.…”
Section: Applicationssupporting
confidence: 68%
“…The augmented segment tree of Mehlhorn and Näher [5] guarantees the existence of a O(N log N log log N )-time algorithm [4]. In fact, a data structure giving a running time of O(N log N log log N ) is likely to be implicit in Gabow, Bentley, and Tarjan [2]; however their result as stated (Theorem 3.3 and the discussion above it) is for the case when all key(i) values are known in advance.…”
Section: Running Time Analysismentioning
confidence: 99%
“…Mehlhorn and Näher [18] have shown that both of these operations can be done in O(log d−1 n) time. Moreover, such a range tree can be built in O(n log d−1 n) time.…”
Section: If Both L(a I ) and L(b Imentioning
confidence: 99%
“…First, the amount of space used by the algorithm is O((1/ d−1 )n log d−1 n). Second, the algorithms in [18] do not work in the algebraic computation-tree model. Thus, even though the running time is O(n log n) in the case when d = 2, the Ω(n log n) lower bound of [8] on the time to compute any spanner does not apply.…”
Section: If Both L(a I ) and L(b Imentioning
confidence: 99%